Numerical analysis of waves attenuation by vegetation in enclosed waters - Mattosinho, G. O.; Maciel, G. F. [UNESP]; Vieira, A. S.; Fortes, C. J.E.M. (Taylor & Francis, 2018)
Numerical simulations using the SWAN-VEG model (Simulating WAves Nearshore, with vegetation module) were performed considering the case of Ilha Solteira (SP) reservoir, a navigable stretch of the Tiete—Paraná waterway. The objective was to analyse the attenuation of wind-generated wave energy by the presence of vegetation in the left margin of reservoir (place of higher simulated wave heights). In this analysis, we varied the vegetation parameter, Vf, different submergence ratios and the wind intensity for NE wind direction. The results pointed up a neglegible influence of mesh size but high wave attenuation coefficients due the presence of vegetation. Application of non-structural measures to the attenuation of waves in these areas is plausible and should be encouraged because in addition to producing high attenuation coefficients, this is in general a cheaper and environmentally friendly solution.